Reinstating the soul in engineering laboratory work: Direct observation assessment method - Aishah, A.B. (2015)
This paper explores a case on the implementation of a new assessment procedure in a second year undergraduate soil mechanics laboratory. This new method emerged as a result of an attempt to constructively align assessment to intended learning outcome when Outcome-based Education is implemented. The new method involves the introduction of direct observation as part of assessment as well the usual assessment via laboratory report. Constructive alignment between assessment and learning outcomes with embedded formative assessment were used as a strategy to ensure active learning to occur. Assessing the learning process of laboratory activities rather than the end product increases the chances for laboratory key objectives to be achieved; hence, this may yield desired learning outcomes from the laboratory experience. The case presented demonstrates that the soul of engineering laboratory work can be reinstated if assessment involving active learning is carefully planned and the skills required in its implementation are acquired.